Nāṭṭuk Kūttuk Kalāniti Pūntāṉ Yōcēppu : kalaiyulaka vāḻkkai varalāṟu - Akastiyar, Es., 1928- (Navaraca Nāṭṭukkūttuk Kalā Maṉṟam, 1981)
Life and art of Pūntāṉ Yōcēppu, b. 1904, Tamil stage artist and director from Sri Lanka.